The 4th Japan Ushimado International Art Festival. - The 3th Japan Ushimado International Art Festival, Ushimado, 1987; The 4th Japan Ushimado International Art Festival, Ushimado, 1988 (Ushimado : Japan Ushimado International Art Festival Office, 1988)
Penone, Giuseppe ; Shapiro, Joel ; Muraoka, Saburo ; Suga, Kishio ; Toyohira, Yoshio ; Takama, Natsuki
The 3th Japan Ushimado International Art Festival, Sanbishin Plaza, Ushimado, 1986 ; The 4th Japan Ushimado International Art Festival, Sanbishin Plaza, Ushimado, 1987
Text English-Japanese
kunstcatalogus
Keywords: Ushimado